An overview of blockchain science and engineering. Issue 6 (3rd June 2020) - Karame, Ghassan; Huth, Michael; Vishik, Claire
Abstract : This is the preface to a special issue in the journal Royal Society Open Science, themed around blockchain technology. Since this is still an emergent and interdisciplinary field, we first provide a gentle introduction into that larger topic. Then, we discuss why this technology has been criticized for not being energy-efficient. Next, we provide an analysis of recent developments in blockchain research that may help with making blockchain technology truly sustainable. Finally, we highlight some of the contributions made by papers in this special issue.